Conservation strategy of Anaphalis spp. in Bromo Tengger Semeru National Park, East Java - Filza Yulina Ade; Luchman Hakim; Estri Laras Arumingtyas; Rodiyati Azrianingsih (Journal of Tropical Life Science, 2021)
The objective of the paper were to identify factors related to conservation strategy of Anaphalis in BTSNP. This study found internal factor related to strength includes the existence of species and value of Anaphalis spp., while the weaknesses include increase of habitat degradation and disturbance caused by tourism activities. The opportunities for conservation includes support of policy in biodiversity conservation and increase of ecotourism movement, while the threats aspect include less control of land uses changes and increase of mass tourism. The SWOT analyses recommends some significant strategy which are derived from combination of enhancing strength to optimizing opportunities, reducing weaknesses and optimizing opportunities, Enhancing strength to reduce threats and managing weaknesses to manage risk. Â